The Boundedness of Intrinsic Square Functions on the Weighted Herz Spaces. (12th January 2014) - Wang, Hua
Abstract : We will obtain the strong type and weak type estimates of intrinsic square functions including the Lusin area integral, Littlewood-Paley𝒢 -function, and𝒢 λ * -function on the weighted Herz spacesK ˙ q α, p ( w 1, w 2 ) ( K q α, p ( w 1, w 2 ) ) with general weights.